Pengembangan Media Pembelajaran Fisika Menggunakan Game Edukasi Pada Kelas Xi Di Madrasah Aliyah Nurul Hidayah Bojonegara - Santosa, Budi; Aribowo, Didik; Irwanto, Irwanto (Program Studi Teknik Elektro Universitas Khairun, 2021)
Verbal delivery of learning and long learning hours causes students to often play games without the knowledge of the teacher during the learning process so that learning outcomes are not optimal to achieve the specified minimum completeness criteria. This study aims to produce educational game learning media and determine student responses to educational game learning media. To be able to produce a certain product, the research steps used the waterfall model. This research was conducted at Madrasah Aliyah Nurul Hidayah Bojonegara in class XI students with data sources on learning outcomes dan syllabus. Data collection techniques used interviews, observation and questionnaires, while data analysis techniques used a likert scale. The results of the research to be achieved are a jigsaw puzzle game as a learning medium, this game is made using the Unity 3D application. from the study also wanted to know student responses about the jigsaw puzzle game as an educational game or learning media.